THE EFFECTIVENESS OF BULLYING PREVENTION EDUCATION ON IMPROVING STUDENTS' UNDERSTANDING AT SDN 1 NEGLASARI - Nabhani, Irfan; Hadita, Akmala; ., Anton; Amelia, Wanda; Tryananda, Muthiara; Faazan, Nazma Barqia; Ubaidillah, Muhammad Fatih; Nandar, Deka Ali (Indonesian Journal of Community Empowerment (IJCE), 2025)
ABSTRACT Bullying is an intentional and repetitive aggressive behavior, whether verbal, physical, or social, that negatively impacts the victim’s psychological condition. This study aimed to evaluate the effectiveness of bullying prevention education in improving students’ understanding at SDN 1 Neglasari. The research employed a descriptive quantitative approach with 59 respondents from fifth and sixth grade. Data were collected through pre-tests, post-tests, and written accounts of personal or peers’ experiences related to bullying. The results showed an increase in students’ understanding from 71.86% to 89.10%, with the highest improvement in verbal and physical bullying. Students’ written experiences revealed that verbal bullying was the most frequently encountered (39%), followed by physical and social bullying, while 44% of students reported never experiencing bullying. Bullying prevention education proved effective in enhancing students’ understanding and serves as a preventive effort to create a safe and child-friendly school environment. ABSTRAK Perundungan merupakan perbuatan yang dilakukan secara terus menerus dan bersifat agresif, mulai dari verbal, fisik, maupun sosial, yang berdampak negatif pada kondisi psikologis korban. Penelitian ini bertujuan mengevaluasi efektivitas edukasi pencegahan bullying dalam meningkatkan pemahaman siswa SDN 1 Neglasari. Metode penelitian menggunakan pendekatan kuantitatif deskriptif dengan 59 responden kelas lima dan enam. Data dikumpulkan melalui pre-test, post-test, serta penulisan pengalaman pribadi atau teman terkait bullying. Hasil menunjukkan peningkatan pemahaman siswa dari 71,86% menjadi 89,10%, dengan peningkatan tertinggi pada bullying verbal dan fisik. Pengalaman tertulis siswa mengungkapkan bullying verbal paling sering dialami (39%), diikuti fisik dan sosial, sementara 44% siswa tidak pernah mengalami bullying. Edukasi pencegahan bullying terbukti efektif meningkatkan pemahaman siswa dan menjadi upaya pencegahan untuk menciptakan lingkungan sekolah yang aman.